Reclaiming our humanity: Believers as sages and performers of the Gospel in the era of the Fourth Industrial Revolution - Joubert, Stephanus J. (HTS teologiese studies, 2020)
New technologies are emerging across the globe and are influencing our perceptions of the world, our behaviour and our understanding of what it means to be a human being. In particular, Klaus Schwab and others define the advancement of ‘cyber-physical systems’, coupled with new capacities for both machines and human beings, in terms of ‘The Fourth Industrial Revolution’. The South African Parliament placed the Fourth Industrial Revolution on its national agenda. It serves as a new foundation story for the country, one that justifies, explains and facilitates the perceived shifts from previous understandings of reality, and one that currently plays out on an unevenly distributed continuum. To be an effective agent of change and a relevant voice for the voiceless and the powerless in this Fourth Industrial Revolution era, the church must facilitate immersive, yet provocative performances of the Gospels while simultaneously embodying and empowering others with wisdom to traverse this unchartered terrain of technological innovation with insight and discernment. The church’s message should be that, to live more godly, we all need to become more human, not post-human or trans-human. We cannot avoid the fact that we are entering an era in which technology will redefine who we are. However, the question is not only what technology can do for us but also what we as change agents should allow technology to do.Contribution: This article focuses on the role of the Christian church in our era of massive technological innovation. The creative role that faith communities could play in order to ensure a more humane approach to and interaction with various 4IR technologies are addressed. A short investigation is offered of a new ‘hermeneutical performance’ of the Bible as an immersive text in an interactive 4IR world. In this regard the emphasis on a new ‘metanoetic alignment with the mission of Jesus, which is explored in the article, links on to the theological scope of HTS Theological Studies in terms of new theological insights and new vistas for academic investigation.